On the Inclusion of Dialectal Phrases in Explanatory Dictionaries - Islomova Shoira Xushboqovna (Periodica Journal, 2025)
This article discusses the criteria developed for the presentation of phrases in explanatory dictionaries and their inclusion in such dictionaries, as well as the principles regarding the presentation of dialectal phrases in dictionaries. (2) Methods: Methods for representing phrases in dictionaries and related issues have been discussed in the scientific literature, and principles for their representation in dictionaries have been developed. In particular, Uzbek scientists have compiled an explanatory dictionary of Uzbek phrases
Keywords: dialect; phraseological unit